2019
DOI: 10.1128/jvi.01311-19
|View full text |Cite
|
Sign up to set email alerts
|

The ESCRT-0 Protein HRS Interacts with the Human T Cell Leukemia Virus Type 2 Antisense Protein APH-2 and Suppresses Viral Replication

Abstract: The divergent clinical outcomes of human T cell leukemia virus type 1 (HTLV-1) and HTLV-2 infections have been attributed to functional differences in their antisense proteins. In contrast to HTLV-1 bZIP factor (HBZ), the role of the antisense protein of HTLV-2 (APH-2) in HTLV-2 infection is poorly understood. In previous studies, we identified the endosomal sorting complex required for transport 0 (ESCRT-0) subunit HRS as a novel interaction partner of APH-2 but not HBZ. HRS is a master regulator of endosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Our findings highlight the functional involvement of the IXXLL motif. These results highlighting the importance of the N-terminal region of APH-2 and are compatible with the study by Martini et al, which identified a similar domain of APH-2 for the interaction with the PSAP domain of HRS [ 27 ]. Although the Tat-mediated transcription was affected in the presence of APH-2, we did not find a specific association between APH-2 and Tat, indicating that HTLV-2 APH-2 may not directly engage HIV-1 Tat to impose its inhibitory effect.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings highlight the functional involvement of the IXXLL motif. These results highlighting the importance of the N-terminal region of APH-2 and are compatible with the study by Martini et al, which identified a similar domain of APH-2 for the interaction with the PSAP domain of HRS [ 27 ]. Although the Tat-mediated transcription was affected in the presence of APH-2, we did not find a specific association between APH-2 and Tat, indicating that HTLV-2 APH-2 may not directly engage HIV-1 Tat to impose its inhibitory effect.…”
Section: Discussionsupporting
confidence: 93%
“…The negative regulator APH-2 crucially controls HTLV-2 replication by influencing transcription [ 6 , 7 ]. Recent studies also explored its role in managing viral release and budding [ 27 ]. Considering the common aspects between HIV-1 and HTLV-2 such as lineage, mode of transcription, replication and the clinical impact of co-infection over the disease progression of HIV-1, there might be a possible intervening effect of viral regulators on replication of one another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to an effect on HBV transcription, HGS can diminish the pool size of intracellular nucleocapsids with ongoing genome maturation, probably in part by promoting the secretion of naked capsids. Recently, HGS was also found to be important in the life cycle of RNA viruses, such as chikungunya virus [65] and HTLV-2 [66]. Table 1.…”
Section: Escrt Machinerymentioning
confidence: 99%
“…The copyright holder for this this version posted December 10, 2021. ; https://doi.org/10.1101/2021.12.08.471876 doi: bioRxiv preprint HBV-particle secretion. Vps4 and the molecular endosomal sorting complexes required for transport (ESCRT) machinery could cooperate in the secretion of the HBV virion (10,11). Cellular kinases can regulate virion formation and promote intracellular capsid accumulation by modifying capsid phosphorylation (12)(13)(14).…”
mentioning
confidence: 99%